2013
DOI: 10.1063/1.4822187
|View full text |Cite
|
Sign up to set email alerts
|

Determining passive cooling limits in CPV using an analytical thermal model

Abstract: Abstract:We propose an original thermal analytical model aiming to predict the practical limits of passive cooling systems for high concentration photovoltaic modules. The analytical model is described and validated by comparison with a commercial 3D finite element model. The limiting performances of flat plate cooling systems in natural convection are then derived and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Passive cooling in point focus systems has been proven to successfully manage the PV cell temperature with different heatsink geometries and for high concentration ratios for up to 2000 suns [35,39]. For ultrahigh concentration ratios, solar cells of 1 mm 2 or smaller can maintain the cell temperature below the maximum recommended operating temperature with a conventional flat-plate heatsink up to 10,000 suns [40].…”
Section: Thermal Receiver Design and Materialsmentioning
confidence: 99%
“…Passive cooling in point focus systems has been proven to successfully manage the PV cell temperature with different heatsink geometries and for high concentration ratios for up to 2000 suns [35,39]. For ultrahigh concentration ratios, solar cells of 1 mm 2 or smaller can maintain the cell temperature below the maximum recommended operating temperature with a conventional flat-plate heatsink up to 10,000 suns [40].…”
Section: Thermal Receiver Design and Materialsmentioning
confidence: 99%
“…Gualdi et al [19] identified the limits of passive cooling for concentration ratios up to 2000 suns. Results showed that a flat heat-sink could maintain the cell temperature below 80 °C for a cell side length between 2-4 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of research show the ability to use passive heat sink to keep panel efficiently (especially in 500suns) [12][13][14][15][16][17][18][19], the passive cooling fin structure can be shown in Figure 3 [19]. The nomenclature used (Figure 3) in the present work is: spacing (s), pitch (p), height (H), thickness (t), length (L), base width (W), and base thickness (tb) [19].…”
Section: Hcpv Typesmentioning
confidence: 99%